THE MORPHOLOGY, STRUCTURAL EVOLUTION AND SIGNIFICANCE OF PUSH MORAINES - Bennett M.R. (My University, 2001)
Push moraines (glaciotectonic ice-marginal moraines) have a restricted distribution at modern glacier margins and consequently are of potential value in reconstructing Pleistocene ice sheets, providing data both on former glaciodynamics and on the palaeoenvironment of the glacial foreland. To the wider earth science community, push moraines are of interest as analogues for thin-skin tectonics within orogenic belts. This paper reviews the morphology, structural geology, formation and significance of push moraines. The morphological and structural characteristics of small, seasonal, push moraines through to large, multi-crested, examples produced by sustained glacier advances are reported, before the primary controls on push moraine formation are examined. These controls include the nature of the applied glacial stress field, the presence and properties of décollement horizons, and the shear strength and rheology of the glacial foreland. A conceptual model of push moraine formation is introduced, in which the range of observed morphological and structural forms are viewed within a matrix defined by the main variables which control their formation. The absence of consensus over which of these variables is of greatest importance currently limits the significance of push moraines in palaeoglaciological research. As a consequence, this review emphasises the need for future research in order to realise the true potential of push moraine in the reconstruction of Pleistocene environments.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен